JmzTab: A Java interface to the mzTab data standard. Issue 11 (29th April 2014) - Xu, Qing‐Wei; Griss, Johannes; Wang, Rui; Jones, Andrew R.; Hermjakob, Henning; Vizcaíno, Juan Antonio
<x xml:space="preserve">Abstract</x> mzTab is the most recent standard format developed by the Proteomics Standards Initiative. mzTab is a flexible tab‐delimited file that can capture identification and quantification results coming from MS‐based proteomics and metabolomics approaches. We here present an open‐source Java application programming interface for mzTab called jmzTab. The software allows the efficient processing of mzTab files, providing read and write capabilities, and is designed to be embedded in other software packages. The second key feature of the jmzTab model is that it provides a flexible framework to maintain the logical integrity between the metadata and the table‐based sections in the mzTab files. In this article, as two example implementations, we also describe two stand‐alone tools that can be used to validate mzTab files and to convert PRIDE XML files to mzTab. The library is freely available at http://mztab.googlecode.com.